Fundamentals of integrated ferrohydrodynamic cell separation in circulating tumor cell isolation. Issue 9 (15th March 2021) - Liu, Yang; Zhao, Wujun; Cheng, Rui; Harris, Bryana N.; Murrow, Jonathan R.; Hodgson, Jamie; Egan, Mary; Bankey, Anastacia; Nikolinakos, Petros G.; Laver, Travis; Meichner, Kristina; Mao, Leidong
Abstract : We present the fundamental theory and experimental validations of an integrated ferrohydrodynamic cell separation (iFCS) method that can isolate circulating tumor cells with a high recovery rate. Abstract : Methods to separate circulating tumor cells (CTCs) from blood samples were intensively researched in order to understand the metastatic process and develop corresponding clinical assays. However current methods faced challenges that stemmed from CTCs' heterogeneity in their biological markers and physical morphologies. To this end, we developed integrated ferrohydrodynamic cell separation (iFCS), a scheme that separated CTCs independent of their surface antigen expression and physical characteristics. iFCS integrated both diamagnetophoresis of CTCs and magnetophoresis of blood cells together via a magnetic liquid medium, ferrofluid, whose magnetization could be tuned by adjusting its magnetic volume concentration. In this paper, we presented the fundamental theory of iFCS and its specific application in CTC separation. Governing equations of iFCS were developed to guide its optimization process. Three critical parameters that affected iFCS's cell separation performance were determined and validated theoretically and experimentally. These parameters included the sample flow rate, the volumetric concentration of magnetic materials in the ferrofluid, and the gradient of the magnetic flux density. We determined these optimized parameters in an iFCS device that led to a high recovery CTC separation in both spiked and clinical samples.